Media Pembelajaran Maharah Kitabah - Lina, Lina; Mahdi, Annisa Luthfiah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Maharah kitabah or writing skills are one of the complex skills. Many factors are characteristic in the aspect of writing Arabic, which are also challenges in achieving these skills, such as the direction of writing and the shape of the letters that are different from Indonesian. This causes maharah kitabah to be a skill that is difficult for students to achieve compared to the other three Arabic language skills. Learning media has a very important role in supporting the development of this skill. However, there are still many educators who do not know the maharah kitabah learning media. This study aims to identify and analyze various learning media that can be used in maharah kitabah learning. The method used in this study is qualitative-descriptive. Data collection techniques by reading and reviewing in depth the results of literature studies related to the topic being studied. The results of this study indicate that there are eleven learning media that teachers can choose for maharah kitabah learning, including crosswords, comics, video clips, posters, radio or television stories, cassette tapes, photos and pictures, internet, songs, pop up books, and word cards. In the process of choosing which media will be used by teachers, there are several criteria that must be considered, such as learning objectives, student targets, media characteristics, time, cost, availability, context of use and technical quality. The teacher's ability to utilize various forms of media will determine the success of student learning.